1991
DOI: 10.1523/jneurosci.11-02-00505.1991
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic responses evoked by mechanical stimulation of the mucosa in morphologically characterized myenteric neurons of the guinea-pig ileum

Abstract: Recordings were made from myenteric neurons of the guinea-pig ileum during reflexes evoked by mechanical stimulation of the mucosa. Impaled neurons were injected with dye (Lucifer yellow or biocytin), and their shapes were determined. All neurons were 5-12 mm from the stimulus, a brush stroke that deformed the mucosal villi. Neurons were classified as S-neurons or AH-neurons (Hirst et al., 1974). About 40% of S-neurons oral to a stimulus responded with bursts of fast EPSPs (average frequency, 15-40 Hz); these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 23 publications
3
107
0
1
Order By: Relevance
“…In isolated segments of guinea pig ileum, it has been shown that mechanical stimulation of mucosal villi generates short bursts of fEPSPs that occurred in the frequency range of 15 − 40 (Bornstein et al 1991). In similar experiments it was shown that if the mechanical stimulus is applied at intervals of less than 10 seconds, the amplitude of fEPSPs declined during repetitive stimulation (Smith et al, 1992).…”
Section: Rundown Of Fepspsmentioning
confidence: 94%
See 1 more Smart Citation
“…In isolated segments of guinea pig ileum, it has been shown that mechanical stimulation of mucosal villi generates short bursts of fEPSPs that occurred in the frequency range of 15 − 40 (Bornstein et al 1991). In similar experiments it was shown that if the mechanical stimulus is applied at intervals of less than 10 seconds, the amplitude of fEPSPs declined during repetitive stimulation (Smith et al, 1992).…”
Section: Rundown Of Fepspsmentioning
confidence: 94%
“…Electrophysiological studies in myenteric neurons maintained in primary culture have shown that nAChRs desensitize much more quickly than P2X receptors expressed by the same neurons (Zhou and Galligan, 1998;Zhou et al, 2002;Brown and Galligan, 2003). Different receptor desensitization rates may have functional significance for the control of GI motility as it has been shown that mechanical stimulation of the mucosa in isolated segments of guinea-pig ileum elicits bursts of fEPSPs that occur at frequencies ranging between 15 − 40 Hz (Bornstein et al, 1991;Smith et al, 1992). Similar bursts of fEPSPs were also elicited when chemical stimulation was applied to mucosa (Bertrand et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1A) [11], and are termed S/uniaxonal neurons in the discussion below. One major role of the AH/Dogiel type II neurons is as intrinsic sensory (or primary afferent) neurons (for reviews see [12,34,35], while S/uniaxonal neurons are interneurons, muscle motor neurons and secretomotor neurons [12,13,113]. However, while this division is convenient, it remains somewhat controversial because AH/Dogiel type II neurons receive excitatory synaptic input (see below) and thus may act as interneurons under some conditions [123,124,133].…”
Section: Types Of Enteric Neuronmentioning
confidence: 99%
“…Modulatory cholinergic (Grider and Makhlouf, 1986;Smith and Fumess, 1988;Tonini and Costa, 1990) and noncholinergic Makhlouf, 1987, 1992; interneurons link the enteric motor neurons to afferent sensory neurons. The sensory neurons activated by muscle stretch and mucosal stimulation are distinct, converging on the same motor neurons (Bornstein et al, 1991a;Smith et al, 1992a). The two populations of sensory neurons can be activated concurrently by muscle stretch and mucosal stimulation leading to augmentation of the efferent response (Smith et al, 199 1;Yuan et al, 1991).…”
mentioning
confidence: 99%